Repatriation from Lithuania SSR in 1956–1959 and Poland secret services. - Stravinskienė , Vitalija (Genocidas ir rezistencija, 2010)
In the mid-1950s, following successful negotiations between the authorities of the People's Republic of Poland and the leadership of the Soviet Union, the process of repatriation from the USSR to the PRP was renewed. Initially, it encompassed repressed individuals, primarily of Polish nationality, who had already served their sentences or had been released early from incarceration. All of them sought to relocate to Poland. The leadership of the USSR agreed to allow approximately 9,000 such individuals to leave.
Keywords: Lithuania; Poland; repatriation; Soviet regime; KGB